Characterization of Al2O3 and SiO2 ultra thin-films deposited by ALD for microfabricated rubidium vapor cells - Cunha, Florival Moura (2022)
The Atomic Layer Deposition (ALD) technique can be used to increase the lifetime of microfabricated rubidium vapor cells (magnetic sensors for magnetoencephalography) by an ultra-thin coating layer deposited on the internal cell walls (Figure 1). The ALD presents excellent control over the ultra thin films thickness (< 20 nm) and allows complex 3D structures to be covered with a high-aspect-ratio coating. This work shows the characterization of alumina (Al2O3) and silicon dioxide (SiO2) ultra-thin films deposited by Thermal ALD (ThALD) and Plasma-Enhanced ALD (PEALD).